Lembaga Pendidikan Islam dan Perubahan Sosial - Bambang Sucipto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Education and social change influence each other, so that a broad impact on society.Education is an institution that can serve as agents of social change and also to determine the direction of social change. Social change is a necessary thing to happen, sooner or later, the changes are positive or negative or other changes. Change is something that we should be grateful at the same time we are aware of because of the changes that will positively impact provide progress and prosperity for mankind, whereas negative changes on the contrary, that destroy human civilization. Islamic educational institutions must be vigilant against the negative effects of social change.Do not let the educational institutions are not ready to sacrifice the learners. Technological advances brought by contemporary civilization, it must be controlled by the stakeholders of educational institutions.This paper will discuss the response of Islamic educational institutions to social change. Keywords: institutions, education, Islam, change, social.